Inovasi Pembelajaran IPS Melalui Pemanfaatan Youtube Sebagai Media Edukasi - Astria Wulandari; Nezha Pangarungan; Firdaus W Suhaeb (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Social studies learning has long been considered boring, memorization-heavy, and lacking context. This study aims to examine innovations in social studies learning through the use of YouTube as an educational medium. The study used a qualitative approach with a literature review method. Data sources were obtained from national and international scientific journal articles from the last 5–10 years, textbooks, and seminar proceedings. Data collection techniques included searching academic databases such as Google Scholar, ERIC, and DOAJ. Data analysis used qualitative content analysis techniques. The results of the study indicate that YouTube has advantages: presenting material visually so that abstract concepts become concrete, easy access anytime and anywhere, increasing student learning motivation, and supporting independent learning. The successful use of YouTube is largely determined by the role of teachers in selecting appropriate content, integrating it with active learning methods, and guiding students to become wise digital users. YouTube is not a substitute for teachers, but rather a tool that strengthens the role of educators. However, this study has limitations because it only used a literature review and therefore did not directly measure the effectiveness of YouTube use in the classroom learning process. Therefore, further research is recommended to conduct field research or experiments to determine the effect of YouTube use on students' learning outcomes and critical thinking skills. In conclusion, YouTube is a potential educational medium for realizing innovative, interesting, and meaningful social studies learning in the digital era